Middle East Respiratory Syndrome (MERS) and Novel Coronavirus Dis- ease-2019 (COVID-19): From causes to preventions in Saudi Arabia (2020)
Saudi Arabia is one of the countries that has been affected by COVID-19. At the beginning of March 2020, it revealed a steadily rising number of laboratory-confirmed cases. By 20th May 2020, 59,854 infected cases had been confirmed, with 329 deaths. To prevent a further outbreak of COVID-19, this article discusses the current understanding of COVID-19 and compares it with the outbreak of Middle East Respiratory Syndrome (MERS) in 2012 in Saudi Arabia. It also discusses the causes, transmission, symptoms, diagnosis, treatments and prevention measures to identify an applicable measure to control COVID-19.